Association Between C-Peptide Level and Subclinical Myocardial Injury - Chen, Ziwei; He, Jing; Ma, Qiang; Xiao, Mingbing (Frontiers in Endocrinology, 2021)
Abstract Background: Previous studies have confirmed an association between C-peptide levels with the risk of cardiometabolic diseases. However, whether circulating C-peptide was related to subclinical myocardial injury (SC-MI) remained unknown. Methods: A total of 3752 participants without a history of cardiovascular diseases were included in our study from National Health and Nutrition Examination Survey III (NHANES III). Multivariable linear regression was performed to explore the correlation between C-peptide and cardiac injury score (CIIS). Multivariate logistic regression was used to examine the association of C-peptide quartile and SC-MI. Results: Circulating C-peptide was significantly associated with CIIS (β:0.09, 95% confidence interval [CI]: 0.00-0.17; p=0.041). Compared with the lowest quartile, the highest quartile of circulating C-peptide increased a 1.48-fold risk of SC-MI (Odds ratio=1.66, 95% CI: 1.18-1.87; p=0.001). Conclusions: The level of C-peptide was independently associated with CIIS and SC-MI, which could serve as a new risk factor of SC-MI.